Development of composites based on residual microalgae biomass cultivated in wastewater. (5th November 2021) - González-Balderas, R.M.; Felix, M.; Bengoechea, C.; Orta Ledesma, M.T.; Guerrero, A.; Velasquez-Orta, S.B.
Graphical abstract: Highlights: Microalgae ultrasound pre-treatment induces strengthening of biocomposites. 20% wt. polycaprolactone reinforced residual Desmodesmus materials. Proteins thermal degradation reduced deformability in residual Tetradesmus materials. Abstract: Ultrasound pre-treatment and protein extraction of Desmodesmus sp. and Tetradesmus obliquus biomass induced residual microalgae/polycaprolactone (PCL) biocomposites with higher viscoelastic and mechanical properties as injection mould temperature increased. This was probably associated to the promotion of microalgae proteins-PCL interactions. The PCL content required, to strengthen the biocomposites, depended on the microalgae system (20 or 10 wt% for residual Desmodesmus sp. (RD) or Tetradesmus obliquus (RT), respectively). Protein degradation was observed in RT-based systems at mould temperatures higher than 100 °C. On the contrary, a greater mould temperature induced thermal crosslinking and certain cell disruption in RD-based systems. These environmentally-friendly biocomposites are an interesting alternative for replacing petroleum plastics.